The Analysis of Understanding in Seismic – Resilient Infrastructure Planning in Vocational Student’s Civil Engineering - Debataraja, Lisherly Reginancy; Silalahi, Oktavia Ully Artha; Sianturi, Fenny Novita Meysabed; Tarigan, Pagit Juni Sartika Br; Badriansyah, Dine Noviandri (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
The analysis of understanding in Seismic-Resilient Infrastructure Planning among vocational students in civil engineering is indispensable for multifaceted reasons. This study employs a questionnaire validation test as a means of data collection, utilizing questionnaires to gather information. Simple random sampling was applied to select respondents from Medan State Polytechnic students in their 5th and 7th semesters. The questionnaire is designed to assess students' knowledge of earthquake-resistant infrastructure planning. The research is structured into three segments, focusing on the understanding of earthquake resistance management, structural earthquake resistance, and infrastructure earthquake resistance. The aspect of management seismic resilience understanding ranges from 3.22% to 9.65%. The highest understanding is observed in the awareness of quality control activities, the fifth assessment (9.65%). The lowest understanding is in reduce errors in the implementation of earthquake-resistant construction, the nineth assessment (3.22%). The aspect of structure seismic resilience understanding ranges from 2.78% to 9.48%. The highest understanding is observed in threaded reinforcement, the fourth assessment (9.48%). The lowest understanding is in earthquake-resistant house construction, the seventh assessment (2.78%). The aspect of infrastructure seismic resilience understanding ranges from 5.57% to 15.83%., The highest understanding is observed in earthquake-resistant foundations, the second assessment (15.83%). The lowest understanding is in post-disaster assessment approach, the fifth assessment (5.57%). These percentages likely represent the level of comprehension or proficiency of students in each respective aspect, with higher percentages indicating a better understanding. It is crucial to analyze these results collectively and over time to identify trends, strengths, and areas for improvement in the seismic resilience education provided to vocational civil engineering students.